Level of Underhand Passing Skills in Volleyball Among Junior High School Extracurricular Participants - Alfi Oktalatifah; Gatot Jariono; Vera Septi Sistiasih (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Underhand passing is a fundamental technique in volleyball that determines the success of ball control and attack development. At the junior high school level, mastery of this technique is an important indicator in extracurricular coaching. This study aims to analyze the level of underhand passing skills among participants in junior high school volleyball extracurricular activities. The study uses a descriptive quantitative approach with 20 students selected through purposive sampling as subjects. The research instrument was an underhand passing skill test covering five assessment aspects: body position, hand use, passing accuracy, speed and agility, and body balance. The data were analyzed using descriptive statistics, expressed in percentages. The results showed that most participants were in the fair to good category, with body position being the most dominant component in the good category. However, the aspects of passing accuracy and body balance still need improvement. It can be concluded that the underhand passing skills of extracurricular participants are at a fairly good level, but are not yet evenly distributed across all technical aspects. This study recommends developing a more specific, evaluation-based training program focused on technical aspects to improve the quality of coaching in a sustainable manner.